Saberes desde lo social Transdisciplinariedad en las realidades sociales - Caicedo-Muñoz, Silvia, María Díaz Rico (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2020)
The Faculty of Psychology of the University of San Buenaventura Cali annually conducts the week Workshops from the social. This academic-pedagogical exercise, which has transcended for 22 years, for this occasion included the third regional psychology meeting Saberes desde lo social: transdisciplinarity in social realities and the first regional symposium Gobiernos, familias e infancias: por el derecho a crecer en familia, in collaboration with the governmental NGO Aldeas Infantiles-Colombia, held on October 17 and 18, 2018.